2013
DOI: 10.1021/la4014784
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Proteins Inside a Hydrophobic Cavity

Abstract: We study the effects of confinement and hydrophobicity of a spherical cavity on the structural and thermal stability of proteins in the framework of a hydrophobic-polar (HP) lattice model. We observe that a neutral confinement stabilizes the folded state of the protein by eliminating many of the open-chain conformations of the unfolded state. Hydrophobic confinement always destabilizes the protein because of protein-surface interactions. However, for moderate surface hydrophobicities, the protein remains stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 43 publications
(56 reference statements)
0
35
0
Order By: Relevance
“…Radhakrishna et al. 2013 reported the influence of crowding and confinement conditions for higher activities associated with the immobilized alcohol dehydrogenase (ADH) in SBA‐15. However in case of CLEC, the enzyme stability is mainly dependent on the crosslinking efficiency, internal mass‐transfer resistance and crowding and confinement environment created by modification of essential amino groups by the cross linking agents such as glutaraldehyde .…”
Section: Discussionmentioning
confidence: 99%
“…Radhakrishna et al. 2013 reported the influence of crowding and confinement conditions for higher activities associated with the immobilized alcohol dehydrogenase (ADH) in SBA‐15. However in case of CLEC, the enzyme stability is mainly dependent on the crosslinking efficiency, internal mass‐transfer resistance and crowding and confinement environment created by modification of essential amino groups by the cross linking agents such as glutaraldehyde .…”
Section: Discussionmentioning
confidence: 99%
“…Also using activity as a gauge for stability, Radhakrishna et al . [69] found that immobilisation on the internal surface of SBA-15 increases the activity and stability of alcohol dehydrogenase. Using computational methods it was determined that the elimination of possible open-chain conformations provides entropic effects enhancing the observed increased stabilisation.…”
Section: Sba-15 As a Carrier Of Biological Therapeuticsmentioning
confidence: 97%
“…Another point worthy of note is that the moderate hydrophobic nanopores are more favorable to the thermal stability of immobilized PCL than the hydrophilic and strong hydrophobic nanopores. 41 They proposed that the surface hydrophobicity of nanopores plays a non-monotonic role in affecting the stability of these immobilized enzymes. 40 Similar trends were observed for alcohol dehydrogenase, lysozyme and myoglobin according to a new study by Belfort and Kumar.…”
Section: Closed-inactivementioning
confidence: 99%
“…41,57,58 This benefits from the restricted space endowed by the fitted nanopores, which can eliminate many of the open-chain conformations of enzyme under adverse conditions. A general conception deriving from massive experimental and theoretical investigations is that a pore size only slightly larger than the enzyme dimensions can effectively improve the enzyme stability against heat and harmful reagents.…”
Section: Promotion Of Enzyme Performance Via Engineering the Spatial mentioning
confidence: 99%